Soil CO2 emission in sugarcane management systems - Moraes Tavares, Rose Luiza; Souza, Zigomar Menezes de; Siqueira, Diego Silva [UNESP]; La Scala Junior, Newton [UNESP]; Panosso, Alan Rodrigo [UNESP]; Costa Campos, Milton Cesar (Taylor & Francis As, 2015)
Sugarcane management systems affect soil attributes such as the carbon cycle. This fact has stimulated the sugar and alcohol industry to refine the sugarcane production systems by replacing the pre-harvest burning (PB) and manual harvest with mechanized harvesting followed by residue deposition. The aim of this study was to evaluate different management systems with respect to C cycling carbon dioxide and soil parameters (chemical, physical and biological) which were determined over the season. Three sugarcane cultivation systems were evaluated at the following periods: (a) PB, (b) 5-year green harvest and (c) 10-year green harvest. The results indicated that CO2 emission was 36% greater in the 10-year sugarcane green harvest system than in the PB system. The bulk density and macroporosity were the factors that were most affected by the different sugarcane management systems and that significantly influenced soil CO2 emissions. The principal component analysis showed that soil CO2 emission was 18% influenced by base saturation (V%) and 14% by pH, especially in the PB area. Additionally, 19% was affected by carbon and macroporosity in the 5- and 10-year green harvest areas, respectively. From our results, it can be concluded that the most CO2 emissions are in the areas of sugarcane green, this is due to the higher carbon concentration when compared with the area of burning sugarcane. The parameters that most influenced the CO2 emissions were bulk density, porosity, macroporosity, pH and V%.
Keywords: Saccharum officinarum; principal component analysis; microbial biomass; chemical attributes; physical attributes